Prefeitura Transparente: plataforma de suporte aos gestores de pequenos municípios para adequação à Lei de Acesso à Informação - Araujo Junior, Antonio Ferreira de (2020)
The present work consists in the creation of a virtual platform, accessible by the internet, which helps managers and technical professionals of small town municipal administrations to make the necessary adjustments in the administration and public management practices to meet the requirements established by the Access Law. the information. This technical-professional report seeks to structure a management model based on the fundamentals of public communication and the various concepts that permeate the universe of transparency, participation and social control.